Mitochondrial behavior when things go wrong in the axon - Pozo Devoto, Victorio M.; Onyango, Isaac G.; Stokin, Gorazd B. (Frontiers in Cellular Neuroscience, 2022)
Axonal homeostasis is maintained by processes that include cytoskeletal regulation, cargo transport, synaptic activity, ionic balance, and energy supply. Several of these processes involve mitochondria to varying degrees. As a transportable powerplant, the mitochondria deliver ATP and Ca2+-buffering capabilities and require fusion/fission to maintain proper functioning. Taking into consideration the long distances that need to be covered by mitochondria in the axons, their transport, distribution, fusion/fission, and health are of cardinal importance. However, axonal homeostasis is disrupted in several disorders of the nervous system, or by traumatic brain injury (TBI), where the external insult is translated into physical forces that damage nervous tissue including axons. The degree of damage varies and can disconnect the axon into two segments and/or generate axonal swellings in addition to cytoskeletal changes, membrane leakage, and changes in ionic composition. Cytoskeletal changes and increased intra-axonal Ca2+ levels are the main factors that challenge mitochondrial homeostasis. On the other hand, a proper function and distribution of mitochondria can determine the recovery or regeneration of the axonal physiological state. Here, we discuss the current knowledge regarding mitochondrial transport, fusion/fission, and Ca2+ regulation under axonal physiological or pathological conditions.